2017
DOI: 10.3346/jkms.2017.32.2.296
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Dental Maturity for a Positive Gonadotropin-Releasing Hormone Stimulation Test Result in Girls with Precocious Puberty

Abstract: Dental maturity is associated with skeletal maturity, which is advanced in girls with central precocious puberty (CPP). We investigated the performance of dental maturity as a screening method for CPP using mandibular second premolar and molar calcification stages, assessed the associated anthropometric and laboratory factors, and evaluated pubertal response predictors using the gonadotropin-releasing hormone stimulation test (GnRHST) in prepubertal and pubertal girls. A prospective case-control study was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Previous studies have reported an association between dental maturity and chronological and bone age. 14,15 The findings of this study showed that a higher tooth formation stage, regardless of the tooth type, was strongly associated with higher chronological and bone age. In this study, the vertical growth of the craniofacial complex, such as lower and total anterior facial heights, was proportional to chronological age, but anteroposterior mandibular growth, ie, total mandibular length and dental maturity of all mandibular teeth, was positively related to the presence or absence of CPP and bone age.…”
Section: Discussionmentioning
confidence: 65%
“…Previous studies have reported an association between dental maturity and chronological and bone age. 14,15 The findings of this study showed that a higher tooth formation stage, regardless of the tooth type, was strongly associated with higher chronological and bone age. In this study, the vertical growth of the craniofacial complex, such as lower and total anterior facial heights, was proportional to chronological age, but anteroposterior mandibular growth, ie, total mandibular length and dental maturity of all mandibular teeth, was positively related to the presence or absence of CPP and bone age.…”
Section: Discussionmentioning
confidence: 65%
“…Suh et al [10] found that accelerated growth rate, advanced bone age, and increased basal gonadotropin and insulin-like growth factor-I (IGF-I) levels were correlated with CPP. Traditional statistical analysis including t test and binary logistic regression were used to select factors correlated with the GnRH test [11-14]. Although remarkable progress has been made in these studies, there is a long way to go for their application in clinics due to the low sensitivity or specificity of tests.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, dental maturation was investigated as a predictive indicator of CPP. 17 However, in another study, girls with CPP showed faster dental maturation, an overgrown maxilla, a horizontal mandibular growth pattern, and vertical excess in the face. 7 In this study, although the differences between the two groups were subtle and clinically insignificant, we demonstrated that girls with CPP exhibited greater posterior facial height and smaller mandibular plane angle than the control group, in linear and angular measurements derived from lateral cephalograms.…”
Section: Discussionmentioning
confidence: 92%